Geology of Antarctica: view from U-Pb geochronology - 外田, 智千; 83822; HOKADA, Tomokazu; 83823 (名古屋大学年代測定資料研究センター, 2014)
2014-03 The Antarctic continent preserves long crustal history from 4.0-3.8 Ga. U-Pb geochronology is one of key issue for understanding the geology of Antarctica. 名古屋大学年代測定総合研究センターシンポジウム報告 departmental bulletin paper